Dengue in Araraquara, state of São Paulo: epidemiology, climate and Aedes aegypti infestation - Ferreira,Aline Chimello (2018)
ABSTRACT OBJECTIVE To describe the epidemiology of dengue in a medium-sized city in the state of São Paulo. METHODS Data, such as circulating serotypes, severe cases and deaths, age group, sex, among others, were obtained on reported and confirmed dengue cases in Araraquara, state of São Paulo, between 1991 and 2015. Climatic and infestation data were also analyzed. These variables were evaluated descriptively, using statistical measures such as frequencies, averages, minimum and maximum. Dengue incidence rates were calculated according to month, year, age and sex, and time series of dengue cases, infestation, and climatic variables. RESULTS Approximately 16,500 cases of dengue fever were reported between 1991 and 2015. The highest number of reports was recorded in 2015 (7,811 cases). In general, the age group with the highest number of reports is between 20 and 59 years old. The highest incidences, generally between March and May, occurred after the increase in rainfall and infestation in January. CONCLUSIONS Increased levels of infestation due to rainfall are reflected in incidence rates of the disease. It is fundamental to know the epidemiology of dengue in medium-sized cities. Such information can be extended to diseases such as Zika and Chikungunya, which are transmitted by the same vector and were reported in the city. The intensification of surveillance efforts in periods before epidemics could be a strategy to be considered to control the viral spread.